Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1108/jdoc-09-2015-0121
|View full text |Cite
|
Sign up to set email alerts
|

Co-construction of meaning, creative processes and digital curation

Abstract: Purpose-The preservation and curation of music with real-time or live electronics is challenging. The goal is not to preserve a recording of the performance but to keep the work alive by providing the means to re-perform them. This paper presents the theoretical and practical outcomes of the Documentation, Dissemination and Preservation of Compositions with Real-time Electronics (DiP-CoRE) project. Design/methodology/approach-The methodology combines methods stemming from work psychology and ergonomics with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…A study investigated music in a live setting as a rational thought process (Boutard, 2016). They found that this form of curation consists of organizing and presenting sounds to create a live performance.…”
Section: Physical Vs Digital Curationmentioning
confidence: 99%
“…A study investigated music in a live setting as a rational thought process (Boutard, 2016). They found that this form of curation consists of organizing and presenting sounds to create a live performance.…”
Section: Physical Vs Digital Curationmentioning
confidence: 99%
“…In addition to technical preservation approaches like migration and emulation, art information professionals have developed methods for documenting the performative and experiential aspects of new media and installation artworks (Jones, 2007). Boutard (2016) has also advocated documentation as a means for preserving a rich and multi-agent record of electronic music performances. Documentation can serve as an ongoing record of an artwork if preservation efforts have failed; but documentation can also inform preservation efforts, providing insight into how an artwork originally functioned.…”
Section: Current Approaches To Preserving New Media Artmentioning
confidence: 99%
“…Methodologically speaking, it provides us with a significant shift from studies that have focused on the documentation of contemporary instrumental (or mixed) music (e.g. Boutard, 2016). While performance may be conceptualized itself as a document, performance-as-document (see Lee, 2018), we will discuss here performance documents and models that may support both documents by intention and documents by attribution (Meyriat, 1981; Roux, 2016), grounding new interpretations of these works.…”
Section: Introductionmentioning
confidence: 99%